Mars and Venus starting over a practical guide for finding love again after a painful breakup, divorce, of loss of a loved one - Gray, John (New York, NY Harper Collins, 1998)
Doubleday Large Print, 10/98
Keywords: Man-woman relationships; Men--Psychology; Women--Psychology; Interpersonal relations